Repositório digital na universidade pública: o caso da Biblioteca Digital de Teses e Dissertações da Universidade do Estado do Rio de Janeiro (UERJ) - Silva, Neusa Cardim da (2011)
It presents an overview of the Graduate Programs in Brazil and at the State University of Rio de Janeiro (UERJ) to contextualize the environment in which the academic production occurs. It discusses the importance of this production in the context of scholarly communication and its presentation in the electronic media, allowing web dissemination. It shows the trajectory of digital libraries and repositories, the concepts, characteristics, functions and movements of open archives - which enabled interoperability between systems and information sharing among scientists and researchers